Glucose oxidase conjugated H2O2 sensitive CdTe QDs: an effective fluorescence tool for glucose sensing - Singh, Pooja; Prabhune, Asmita; Ogale, Satishchandra B.; Guin, Debanjan (Journal of Materials Chemistry B, 2013)
Water-soluble quantum dots (QDs) are extensively used for molecular sensing because of the flexibility they offer in terms of modification of the QDs surface with a variety of functional groups using thiol chemistry and monitoring by fluorescence intensity. We describe a simple assay that allows the photoluminescence (PL) detection of H2O2 and glucose in aqueous samples and demonstrate its applicability by estimating glucose in blood. To enable the glucose detection, we functionalized the 3-mercaptopropanoic acid (MPA) capped CdTe QDs with glucose oxidase (GOx), the enzyme specific to b-D-glucose, using carbodiimide chemistry. The fluorescence of the GOx-functionalized CdTe QDs was quenched on the interaction with glucose. The same photoluminescence quenching was also observed in gel form, when a GOx modified CdTe QDs loaded agarose gel was dipped in H2O2 and glucose solutions, respectively.